Clinical and Investigation Profile of Subacute Sclerosing Panencephatitis (SSPE): An Analysis of Twenty Cases - Saha, NC; Sultana, N; Mollah, MAH; Yasmin, L; Anwar, S (Journal of Dhaka Medical College, 2010)
Objective: To identify common clinical features, sociodemographic characteristics and laboratory parameters of diagnosed cases of Subacute Sclerosing Panencephalitis. Design: Cross sectional descriptive type of study. Setting: Department of Paediatrics, Dhaka Medical College Hospital. Study period: January 2006 to December 2008. Subjects: Twenty clinically diagnosed patients of SSPE. Results: The mean age at presentation was 8 years. Male: Female ratio was 19:1. Most of the patients came from lower socio-economic group (70%). Forty five percent had history of primary measles infection and seventy percent were vaccinated against measles. Most common presenting features were fall to ground (95%), cognitive decline (85%), myoclonic seizures (80%), altered speech (70%), gait disturbance (60%), personality changes (55%), dysphagia (50%) and less commonly blindness (20%). EEG showed abnormal findings in 100% of patients who underwent this test. Measles specific IgG antibody in CSF was positive in 90% cases. Neuroimaging findings were abnormal in 43% cases. Conclusion: The diagnosis of SSPE should be considered in children presenting with deteriorating milestones of development especially cognition and behavior, fall to ground along with myoclonic jerks in an endemic country for measles infection. Investigations like CSF and serum antibody to measles virus and characteristic EEG changes may help further in the diagnosis. Key words: SSPE; Myoclonic jerks; Milestones regression; Measles antibody; EEG. DOI: 10.3329/jdmc.v17i2.6586 J Dhaka Med Coll. 2008; 17(2) : 72-77